Thermal ablation for ata intermediate-risk papillary thyroid carcinoma: efficacy and safety outcomes in a retrospective cohort - Cong, Tian-hao; Wei, Ying; Zhao, Zhen-long; Cao, Shi-liang; Yu, Na; Wu, Jie; Zhou, Xin-yi; Zhao, Han-xiao; Peng, Li-li; Li, Yan; Yu, Ming-an (Frontiers in Endocrinology, 2025)
PurposeTo evaluate the efficacy and safety of thermal ablation (TA) for ATA intermediate-risk papillary thyroid carcinoma (PTC).Methods and materialsThis retrospective study analyzed ATA intermediate-risk PTC (either ultrasound extrathyroidal extension or cervical lymph node < 3cm metastasis) patients treated with TA at China-Japan Friendship Hospital between April 2018 and December 2023. Outcomes included technical success, recurrence-free survival (RFS), and complications. Multi-Cox regression identified prognostic factors.ResultsA total of 113 people were included. TA demonstrated 100% technical success and complete ablation rates. 18 patients (15.9%) had developed tumor recurrence. The 1-, 3-, and 5-year RFS rates were 95.6%, 83.7%, and 79.8%, respectively. Metastatic lymph node diameter independently predicted progression (HR:3.20, p<0.05). Complications occurred in 21.2% of cases, with 1.8% permanent vocal cord paralysis.ConclusionsTA shows promising efficacy and safety for selected ATA intermediate-risk PTC patients, with lymph node size as a key prognostic factor.